2016
DOI: 10.1302/2046-3758.510.bjr-2016-0004.r2
|View full text |Cite
|
Sign up to set email alerts
|

Age-related effects on osteoclastic activities after orthodontic tooth movement

Abstract: ObjectivesTo elucidate the effects of age on the expression levels of the receptor activator of the nuclear factor-κB ligand (RANKL) and osteoclasts in the periodontal ligament during orthodontic mechanical loading and post-orthodontic retention.Materials and MethodsThe study included 20 male Sprague-Dawley rats, ten in the young group (aged four to five weeks) and ten in the adult group (aged 18 to 20 weeks). In each rat, the upper-left first molar was subjected to a seven-day orthodontic force loading follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…The rising number of adults demanding orthodontic treatment presents a new challenge. A previous study found that adults alveolar bone remodeling is much slower than in juveniles due to decreased cellular activity and vascularity, this suggests that orthodontic treatment duration may be longer in adults due to a delay in orthodontic tooth movement (OTM) 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The rising number of adults demanding orthodontic treatment presents a new challenge. A previous study found that adults alveolar bone remodeling is much slower than in juveniles due to decreased cellular activity and vascularity, this suggests that orthodontic treatment duration may be longer in adults due to a delay in orthodontic tooth movement (OTM) 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Osteoblast activity was elevated indicated that there is a new bone formation. To prevent relapse, osteoblast is required to consistently stimulate bone formation [15]. Osteoblasts consequently fill the trenches and tunnels of bone in the surfaces of the bone formed by osteoclasts, through generating novel bone matrices within them and initiate bone apposition [16].…”
Section: Resultsmentioning
confidence: 99%
“…Johnston’s research 34 reported that excess growth of the mandible during this period would lead to mesial drift of the maxillary molars to establish a stable molar relationship for dentoalveolar compensation, which could explain why the upper molars of younger patients drifted mesially to a greater degree after premolar extraction. Moreover, the age-related effects on tissue reaction 57 , the proliferative rate of PDL cells 58 , osteoclastic activities 59 and mineral density in alveolar tissues 60 could explain the greater drift in the younger population.…”
Section: Discussionmentioning
confidence: 99%